Pylorus-Preserving Gastrectomy for Gastric Cancer - Oh, Seung-Young (J Gastric Cancer, 2016)
Pylorus-preserving gastrectomy (PPG) is a function-preserving surgery for the treatment of early gastric cancer (EGC), aiming to decrease the complication rate and improve postoperative quality of life. According to the Japanese gastric cancer treatment guidelines, PPG can be performed for cT1N0M0 gastric cancer located in the middle-third of the stomach, at least 4.0 cm away from the pylorus. Although the length of the antral cuff gradually increased, from 1.5 cm during the initial use of the procedure to 3.0 cm currently, its optimal length still remains unclear. Standard procedures for the preservation of pyloric function, infra-pyloric vessels, and hepatic branch of the vagus nerve, make PPG technically more difficult and raise concerns about incomplete lymph node dissection. The short- and long-term oncological and survival outcomes of PPG were comparable to those for distal gastrectomy, but with several advantages such as a lower incidence of dumping syndrome, bile reflux, and gallstone formation, and improved nutritional status. Gastric stasis, a typical complication of PPG, can be effectively treated by balloon dilatation and stent insertion. Robot-assisted pylorus-preserving gastrectomy is feasible for EGC in the middle-third of the stomach in terms of the short-term clinical outcome. However, any benefits over laparoscopy-assisted PPG (LAPPG) from the patient's perspective have not yet been proven. An ongoing Korean multicenter randomized controlled trial (KLASS-04), which compares LAPPG and laparoscopy-assisted distal gastrectomy for EGC in the middle-third of the stomach, may provide more clear evidence about the advantages and oncologic safety of PPG.